2 - Makerere’s Myths, Makerere’s History: A Retrospect - Sicherman, Carol (Journal of Higher Education in Africa, 2008)
Stemming from the author’s experience of writing a history of Makerere, this paper examines how the myths that have grown up around the university in the eighty-five years since its founding have obscured a clear view of the evolving institution, which the paper defines as ‘a university in Africa’ rather than ‘an African university’. The first myth, of an egalitarian paradise enjoyed by fully- funded students, was questioned even during its heyday by intellectuals disillu- sioned by the failure during the 1960s to fulfil the late-colonial dream. In the aftermath of the tormented 1970s and 1980s, a variant myth declared that new funding formulas made Makerere even more egalitarian. Proponents of this myth claimed that anyone who qualified for admission could attend; however, since government scholarships went to increasingly smaller proportions of the student body, only those who could raise the necessary funds themselves could take ad- vantage of the supposedly widened access. After questioning the meaning of ‘Af- rican’ in a socio-political context still strongly flavoured by foreign influence, the paper moves to consider the challenges that researchers may encounter in writing about universities in Africa: challenges that differ according to whether the re- searcher is an insider or outsider. The paper ends by asking what African academ- ics can do to rid Makerere of the diseases threatening its institutional health.